Keunikan Suku di Indonesia dalam Mempersatukan Bangsa ditengah Perbedaan Budaya - Djenap Zamilummi Polhaupessy; Edy Soesanto; Nazwa Maharani (Journal of Creative Student Research, 2025)
Ethnic and cultural diversity is not only a characteristic of Indonesia, but also part of national identity. Indonesia is known as a country with extraordinary tribes and cultures. Consisting of more than 300 ethnic groups and 700 regional languages. Indonesia is a clear example of the motto "Bhinneka Tunggal Ika" which means "Diverse but still one". This diversity is not a challenge, but rather a wealth and strength that makes Indonesia unique in the eyes of the world. However, amidst cultural richness, the challenge of maintaining social harmony is a necessity that cannot be ignored. These challenges include discrimination and intolerance, globalization and westernization, and so on. Providing the above resistance, efforts are needed to maintain harmony amidst diversity through multicultural education, intercultural dialogue, and also involving the government and mass media. However, sometimes these differences actually cause divisions between nations.